Investigating the Macro Perspective Affecting the Passing Rate in Board Examinations: A Take-off Point in Designing a Causal Model - Baang, Milger A. (International Journal of Learning, Teaching and Educational Research, 2016)
Tagoloan Community College is now challenged with producing graduates who are globally competitive, most especially graduates who are going to take board examinations. The study aimed to investigate the factors affecting the board examination performance of TCC in the board examinations. This study used the descriptive method of research, using a researcher-made questionnaire, focused group discussion and guided interviews to gather data. With three sets of respondents, adding up to a total of 147, it was found out that among the three courses (Criminology, BEED and BSED), and in the four years that TCC took part in the board examinations, the passing rate achieved was never below the National Passing Rate. The performance of TCC can be said to have started unsatisfactorily, but has been improving to render a good to a very good performance level. When the data gathered from all the sets of respondents were summarized, it was found out that it was the internal and stable factors over which the examinees can exercise an amount of control that affect their performance. It is the “Moving Automobile Causal Model” that best fits and represents the factors that have direct effect on the performance of TCC. Another model was also created, the “Airplane Taking-Off Model”, to show all the attributions that are perceived by the respondents and are proven by other researches to have bearing on the results of the board examinations. Two review programs are proposed to be implemented by TCC.